A tale of two cities: Cyclical movements in price and productivity in mining and manufacturing - Bloch, Harry (Centre for Research in Applied Economics, Curtin Business School, 2008)
Data from the mining and manufacturing sectors of the Australian and Canadian economies are used to illustrate the divergent cyclical behaviour of prices and productivity. Productivity in manufacturing is observed to move in the same direction as demand shocks. The opposite is found in mining. Why?This paper provides an explanation of the observed difference in the behaviour of prices and productivity in the mining and manufacturing sectors of industrialized economies. The explanation focuses on a dichotomy of competitive conditions. Manufacturing characterized by equilibrium with sunk costs and reasonably free entry, while mining is characterized by heterogeneity of resource deposits that impedes establishment of an equivalent equilibrium.The long-run equilibrium in manufacturing is associated with firms operating on the declining portion of the long-run cost curves, so demand shocks lead to cost changes in the opposite direction. Heterogeneity in mining operations is associated with fringe firms that act as price-takers and operate along the rising part of their marginal cost curves, which implies a positive impact of demand shocks on marginal cost, and on average cost when the firms are profitable with price exceeding minimum average cost. As average cost is inversely related to average productivity, demand shocks are expected to have a generally positive impact on productivity in manufacturing but a generally negative impact on productivity in mining.